In the footsteps of Joseph II. The potential of the new tourist route of the countries of the former Habsburg Empire from the perspective of cultural heritage tourism - Agnieszka Bogdal-Brzezinska (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: The aim of the article is to present the tourist potential of the routes of rulers' journeys in the territories of modern countries belonging to former empires. The second goal is to design the trail "In the footsteps of Joseph II Habsburg" through the lands of the then empire. Materials and methods: The conditions and the context of cultural tourism were related to issues of historical heritage. The point of reference was the specificity of tourist routes following the footsteps of historical figures. Results: As an example, a proposal for a tourist route in the footsteps of Emperor Joseph II Habsburg was presented, analyzing and selecting his journeys around the Habsburg Empire in the years 1765-1790, indicating the legitimacy of cross-border cooperation to use its high tourist potential. Conclusions: The analysis shows that EU membership is favorable to countries (Central European and Balkan) that want to deepen their international tourist recognition, and to use their common past in the structures of the (Habsburg) empire to create cultural heritage routes analogous to international tourist routes.